Effects of teacher sexual relationship with learners on the delivery of HIV/AIDS programmes in schools : focus on two High Schools in Rundu - Katjiua, John Bosco (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.